Morphine Exacerbates Experimental Colitis-Induced Depression of Nesting in Mice - Cheatham, Stanley M.; Muchhala, Karan H.; Koseli, Eda; Jacob, Joanna C.; Komla, Essie; Negus, S. Stevens; Akbarali, Hamid I. (Frontiers in Pain Research, 2021)
Opioids and non-steroidal anti-inflammatory drugs (NSAIDs) are excellent analgesics, but recent clinical evidence suggests that these drugs might worsen disease severity in Crohn's disease patients, limiting their clinical utility for treating Inflammatory Bowel Disease (IBD). One indicator of change in well-being from conditions such as IBD is behavioral depression and disruption to activities of daily living. Preclinical measures of behavioral depression can provide an indicator of changes in quality of life and subsequent modification by candidate analgesics. In mice, nesting is an adaptive unconditioned behavior that is susceptible to disruption by noxious stimuli, and some types of pain related nesting depression are responsive to opioid and NSAID analgesics. Here we show that a 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) model of experimental colitis depresses nesting behavior in mice, and we evaluated effects of morphine, an opioid, and ketoprofen, a NSAID, on TNBS-induced nesting depression. In Swiss Webster mice, TNBS significantly reduced nesting that peaked on Day 3 and recovered in a time-dependent manner with complete recovery by Day 7. In the absence of colonic inflammation, daily treatment with morphine (1–10 mg/kg) did not decrease nesting except at 10mg/kg/day. However, in TNBS-treated mice 3.2 mg/kg/day morphine significantly exacerbated TNBS-induced nesting depression and delayed recovery. While 3.2 mg/kg/day morphine alone did not alter locomotor activity and TNBS-induced depression of locomotion recovered, the combination of TNBS and 3.2 mg/kg/day morphine significantly attenuated locomotion and prevented recovery. Daily treatment with 3.2 or 10 mg/kg ketoprofen in TNBS-treated mice did not prevent depression of nesting. These data suggest that opioid analgesics but not NSAIDS worsen colonic inflammation-induced behavioral depression. Furthermore, these findings highlight the importance of evaluating analgesic effects in models of colonic inflammation induced depression of behavior.